The law of success - Hill, Napoleon, 1883-1970 (Penguin Audio, Magn Publishing, 2010)
Outlines the author's mind-power method for success as based on interviews with high-achieving people from all walks of life, in a single-volume edition of his original 1928 series that imparts fifteen core lessons about pursuing one's goals.